Windows XP Digital Music for Dummies - Williams, Ryan (Wiley Publishing, 2011)
Now you can give new meaning to the description “High-performance computer!” And you can even choose the performers—Elvis or Elton, the Beatles or Beethoven, Eminem or Englebert, Pfish or Pavarotti. Your Windows XP is like a concert hall, and Windows XP Digital Music For Dummies is just the ticket to get you in and get you enjoying digital music. It will help you get in tune with the times with note-by-note information on: